2022
DOI: 10.3389/fmolb.2022.817735
|View full text |Cite
|
Sign up to set email alerts
|

Identifying SARS-CoV-2 Lineage Mutation Hallmarks and Correlating Them With Clinical Outcomes in Egypt: A Pilot Study

Abstract: The SARS-CoV-2 pandemic has led to over 4.9 million deaths as of October 2021. One of the main challenges of creating vaccines, treatment, or diagnostic tools for the virus is its mutations and emerging variants. A couple of variants were declared as more virulent and infectious than others. Some approaches were used as nomenclature for SARS-CoV-2 variants and lineages. One of the most used is the Pangolin nomenclature. In our study, we enrolled 35 confirmed SARS-CoV-2 patients and sequenced the viral RNA in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Our analysis showed that the beta variant was not detected in Egypt, and the number of alpha variants was limited. Previous studies showed that the prevalence of both C.36 lineages with L452R substitutions and 69–70 del substitutions was high in Egypt at the time of alpha and beta variants [ 14 – 16 ] indicated that C.36 lineages were predominant and acquired several mutations known to confer an adaptive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that the beta variant was not detected in Egypt, and the number of alpha variants was limited. Previous studies showed that the prevalence of both C.36 lineages with L452R substitutions and 69–70 del substitutions was high in Egypt at the time of alpha and beta variants [ 14 – 16 ] indicated that C.36 lineages were predominant and acquired several mutations known to confer an adaptive advantage.…”
Section: Discussionmentioning
confidence: 99%